2005
DOI: 10.1128/aem.71.1.270-275.2005
|View full text |Cite
|
Sign up to set email alerts
|

Different Inactivation Behaviors of MS-2 Phage and Escherichia coli in TiO 2 Photocatalytic Disinfection

Abstract: Despite a wealth of experimental evidence concerning the efficacy of the biocidal action associated with the TiO 2 photocatalytic reaction, our understanding of the photochemical mechanism of this particular biocidal action remains largely unclear. It is generally accepted that the hydroxyl radical (·OH), which is generated on the surface of UV-illuminated TiO 2 , plays the main role. However, our understanding of the exact mode of action of the hydroxyl radical in killing microorganisms is far from complete, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
278
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 482 publications
(283 citation statements)
references
References 24 publications
5
278
0
Order By: Relevance
“…Malondialdehyde (MDA) is released as a product of membrane degradation. It has been suggested that the free radicals •OH and H 2 O 2 were responsible for killing close to the TiO 2 , with H 2 O 2 acting at a distance (118,(148)(149)(150)(151)(152). Direct oxidation of bacterial components is feasible when cells are in direct contact with the surface of TiO 2 .…”
Section: In Vitro Evaluation Of Tio 2 Antibacte-rial Activitymentioning
confidence: 99%
“…Malondialdehyde (MDA) is released as a product of membrane degradation. It has been suggested that the free radicals •OH and H 2 O 2 were responsible for killing close to the TiO 2 , with H 2 O 2 acting at a distance (118,(148)(149)(150)(151)(152). Direct oxidation of bacterial components is feasible when cells are in direct contact with the surface of TiO 2 .…”
Section: In Vitro Evaluation Of Tio 2 Antibacte-rial Activitymentioning
confidence: 99%
“…The following series of elementary reaction steps (Eqs. 1-8) are a simplified for reactions involving ZnO [10]: [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, no matter what oxidant was produced by VUV photolysis, it would not be consumed by the purification process due to the long distance (several millimeters) [31]. On the other hand, Cho et al reported the difference of efficiency among waterborne pathogens by reactive oxygen species [32][33][34][35][36][37]. These studies indicate that bacteria could be inactivated by all forms of reactive oxygen species produced by photocatalysis, while viruses demonstrate notably higher resistance to photocatalytic inactivation.…”
Section: Test Methods For Evaluation Of the Water Purification Abilitymentioning
confidence: 93%